Comparison of placement time duration between precordial lead of ECG Safone and Standard ECG - Firliany Triamanda; Rismadefi Woferst; Wan Nishfa Dewi (Jurnal Keperawatan, 2022)
Introduction: The misplacement of precordial electrodes in the electrocardiography (ECG) recording sometimes occurs in the field. Therefore, it needs a simple and easy use of precordial electrodes of ECG that can determine the position of the precordial electrodes fast and accurately. Objectives: This study aimed to compare placement time duration between the precordial lead of ECG SafOne and the precordial lead of standard ECG. Methods: This study employed an experimental study design with a post-test-only equivalent group method. There were 30 subjects involved in this study who were selected using purposive technic sampling. All-time durations of precordial lead placement gained from subjects using both ECG SafOne and standard ECG were identified and measured. Data were analyzed using Wilcoxon signed-rank test to compare the precordial lead of ECG SafOne and standard ECG. Results: The results showed that most subjects involved were elderly (56-65 years old) (46,7 %) and most were male (60%). The result of this study showed that the average placement time duration for ECG SafOne precordial lead is 52,90 seconds, while standard ECG precordial lead is 152,9 seconds. Based on bivariate analysis, there is a remarkable difference in the placement time duration of precordial lead between ECG SafOne and standard ECG with a p-value of 0,000 < α (0,05). Conclusions: The time duration of precordial lead placement of ECG SafOne is significantly faster than standard ECG. To some extent, the result of this study has a beneficial implication for health care professionals in terms of providing professional services by reducing the time to record electrocardiography.